Inspiring Islamic Education: Enhancing Class 9 Motivation with Creative YouTube Lessons: Pendidikan Akhlak dan Akidah yang Kreatif: Meningkatkan Motivasi Belajar Kelas 9 Melalui Media YouTube di Madrasah Sanawiah Sidoarjo - Ayu Diana Putri; Ainun Nadlif (Universitas Muhammadiyah Sidoarjo, 2023)
This descriptive qualitative research aims to investigate the creativity of Aqidah Morals subject teachers in fostering students' learning motivation through YouTube media in the ninth grade of MTs Ma'arif Kedungkendo. The study also aims to identify the support and barriers faced by Akhlaq subject teachers in utilizing YouTube media to enhance students' learning motivation. The informants of the study consisted of the school principal, subject teachers, and ninth-grade students. Data were collected through interviews, observations, and document analysis. The analysis and interpretation of the data followed Lexy J. Moleong's analytical model, including data reduction, data presentation, and drawing conclusions. The findings indicate that the use of interactive video media through YouTube has increased students' enthusiasm and interaction during the learning process, leading to noticeable improvements in student learning outcomes. The primary supporting factor identified was the full support and facilitation provided by the school's administration, particularly the head of the madrasa, who consistently encouraged teachers' innovative approaches. However, a lack of adequate facilities, such as a school projector, posed as an inhibiting factor, making the implementation of YouTube media challenging within the school setting. The implications of this study highlight the importance of integrating creative multimedia tools, like YouTube, to enhance student engagement and learning motivation in Aqidah Morals education. Highlights: Utilizing YouTube for Learning: Explore the use of YouTube media in Aqidah Morals education to enhance students' learning motivation. Student Engagement and Interaction: Investigate how interactive video content on YouTube can increase students' enthusiasm and foster active participation in the learning process. Support and Barriers: Identify the factors that support and hinder the implementation of YouTube media, including administrative support and the availability of necessary facilities. Keywords: Aqidah Morals, Learning Motivation, YouTube Media, Ninth Grade, MTs Ma'arif Kedungkendo